ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR (Studi Empiris Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2016) - Iva Yuniasih, 14.05.52.0001; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2018)
The purpose of this reseach is to test the influence of leverage, profitability, assets growth and firm size to the dividend policy. This research has been carried out by using quantitative approach and multiple linier analysis method. The data is the secondary data which has been obtained from manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2016 periods. The data collection technique has been done by using documentation and literature study. The sampling has been done by using purposive sampling.The result of this research indicate that Firm Size have positive influence on Dividend Policy. Whereas Leverage, Profitability and Assets Growth have no influence on Dividend Policy.Keywords: Manufacturing Industry, Leverage, Profitability, Assets Growth, Firm Size on Dividend policy